Changes in body dissatisfaction and dieting, and its association with mental health problems among Japanese eighth year adolescents: a 11-year time trend study - Hamada, Shoko; Kaneko, Hitoshi; Ogura, Masayoshi; Sourander, Andre (BMC, 2025)
Background
This study examined the time trends of body dissatisfaction and dieting among Japanese adolescents and the possible associated mental health problems.
Methods
Two cross-sectional studies were conducted in 2011 and 2023 in the same 17 schools in one prefecture of Japan. Participants comprised 1865 (a 92.8% response rate) and 1174 (a 71.5% response rate) eighth grade students, who participated in the 2011 and 2023 surveys, respectively. Body dissatisfaction and dieting were assessed via a scale that assesses eating behavior and dieting. Mental health problems were assessed via the Strengths and Difficulties Questionnaire (SDQ).
Results
The total score on items for eating behavior and dieting did not change between 2011 and 2023. Moreover, no significant interaction was observed between gender and years surveyed. The associated factors measured in the SDQ were similar in 2011 and 2023. An item-level analysis revealed an increase in score of items related to dieting, the fear of getting fat, and wanting to lose weight by not eating among male adolescents. Furthermore, among females, an increase was observed in items on experiences of losing weight and a decrease in items related to dissatisfaction with body image.
Conclusions
The extent of body dissatisfaction and dieting remained stable among Japanese adolescents from 2011 to 2023. Those who were dieting or had eating problems reported higher emotional problems. More males reported dieting and fear of getting fat in the 2023 survey than was reported in 2011. Future studies should conduct surveys in Asian countries other than Japan, including low- and middle-income countries.